Large bowel obstruction in a 27-year-old woman caused by a sigmoid faecal bolus. (14th May 2018) - Smith, Radford Arran James; Abdalkoddus, Muhammad; Bethune, Robert
Abstract : A 27-year-old woman presented to the emergency department with a 24-hour history of severe left iliac fossa pain associated with vomiting. She reported a history of ovarian cysts and was provisionally diagnosed with a ruptured ovarian cyst and admitted under the obstetrics and gynaecology team for further investigation. 24 hours later, she became haemodynamically unstable with increasing abdominal distention and developed a metabolic acidosis. A CT scan revealed large bowel obstruction (LBO) secondary to a faecal bolus in the sigmoid colon with appearances suggestive of adult-onset Hirschsprung's disease. She underwent an emergency laparotomy and decompressive transverse colotomy and was admitted to the intensive care unit overnight. After discharge, she presented again with small bowel obstruction (SBO) which resolved with conservative management. A follow-up colonoscopy and biopsies showed no anatomical abnormalities to account for the LBO and were inconclusive for Hirschsprung's disease.